PENGGUNAAN METODE KAPASITAS KALOR TERGABUNG UNTUK MENENTUKAN WAKTU KRITIS PEMASANGAN BUSHING MESIN TIRE CASTING - Muhammad Is Subekti (Jurnal Elektra, 2019)
As known when installing bushing to the housing, the installation speed is a factor that is a concern for successful installation, because the delay in installation time will result in bushings expanding over the diameter of the housing where the bushings cannot fit into the housing hole and need to shrink back so that the bushing can re-enter which of course will require more time. This will reduce installation efficiency. Therefore, this research will develop a method for determining the critical timing of bushing, so that it can be used as a reference for technicians to allocate installation time.Cooling bushing is doneby using a mixture of Alcohol 90% and dry ice to obtain the final cooling temperature of – 50oC with the area of convection, radiation and volume respectively: 0.445 m2, 0.223 m2 and 0.0018 m2. The method used is a combined heat capacity method where the principle of balance energy, bushing is modeled as an object covered by air fluid at a temperature of 29oC and an initial temperature of – 50oC, then the time of transient bushing to reach – 26oC when it occurs right formulated numerically with the help of software Excel obtained a transient (critical time) time value of 270 seconds (4.5 minutes) at – 26oC.